Perancangan Batik Cap Dengan Corak Wedangan Tradisional Indonesia - Anggi Artiwi; Theresia Widyastuti (Pusat Penerbitan LP2MPP ISI Denpasar, 2021)
Batik is one of the unique traditional fabrics from Indonesia, its uniqueness can be seen from a variety of motifs that have their own meaning. In terms of motifs, batik usually has motifs that are thick with the philosophy of life. The popularity of batik began to grow at the end of the 18th century or early 19th century. Starting from the writing technique to develop into the canting stamp technique. The emergence of stamped batik marked the era of industrialization. Since the era of industrialization and globalization which introduced automation techniques. In this design, the author wants to develop batik motifs with Indonesian Traditional Wedangan motifs. Indonesian traditional Wedangan is one of the cultural heritages, Wedangan is a typical Indonesian drink and drink that is popular with the public, but its position has begun to be shifted and unable to compete with more modern drinks, therefore this batik design was made to reintroduce the tradition of drinking traditional Wedangan. Batik stamps with traditional Indonesian wedangan patterns have never existed before, so this design is a differentiator from various types of motifs on the market. Stamped batik is used in the process of making this batik work because the production process requires a relatively faster time and can produce more. Therefore, in accordance with the design approach from the elaboration of Clipson's Theory regarding the creation of this work textile design, it is well considered from the identification of problems, analysis of production planning, creative processes, production processes and marketing distribution.